Urbanization gradient, diet, and gut microbiota in Sub-Saharan Africa: a systematic review - Paulo, Linda Simon; Msema Bwire, George; Klipstein-Grobusch, K.; Kamuhabwa, Appolinary; Kwesigabo, Gideon; Chillo, Pilly; Asselbergs, Folkert W.; Lenters, Virissa C. (Frontiers in Microbiomes, 2023)
Introduction As Sub-Saharan Africa (SSA) undergoes rapid urbanization changes in diet and lifestyle have contributed to a rise in non-communicable diseases (NCDs) across the region. Changes in gut microbiota which play an important role in human health may be an underlying driving factor. While evidence suggests that the gut microbiota differs between the extreme levels of economic development (least vs highly developed), it is not well-established which factors along the urbanization gradient are most influential, especially for SSA. This systematic review analyzed published articles from SSA countries that examined the differences in the composition and diversity of gut microbiota along the urbanization gradient. The findings of this review have important implications for understanding the impact of urbanization on human health in the SSA. Methods Peer-reviewed articles that examined the link between the urbanization gradient, dietary patterns, and gut microbiota using culture-independent techniques were included in the review. Results A total of 3,265 studies were identified and screened. Eighty-nine (89) studies underwent full-text review, and 23 studies were extracted and included for final analysis. Among these studies, it was observed that hunter-gatherers had high alpha diversity (within-person variation) and beta diversity (between-person variation) in their gut microbiota compared to rural and urban residents in SSA. However, there were inconsistent differences between rural and urban at the individual taxa levels, potentially due to limited statistical power and large variability in the study techniques and designs. Similarly, there were no clear differences in the relative abundance of genera across the urbanization gradient. Additionally, both diet and intestinal parasites were associated with the composition and diversity of the gut microbiota. Conclusion The review revealed there are variations in both alpha and beta diversity of the gut microbiota across the urbanization gradient with a higher diversity observed in rural areas. However, we did not observe significant differences in the relative abundance at phyla or genus levels consistently across the urbanization gradient. Moreover, our findings suggest that the mode of subsistence, diet, and intestinal parasites play a role in shaping the composition and diversity of the gut microbiota in SSA. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021251006, identifier CRD42021251006.